Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3324/haematol.2014.105809
|View full text |Cite
|
Sign up to set email alerts
|

Targeted shRNA screening identified critical roles of pleckstrin-2 in erythropoiesis

Abstract: ABSTRACTliver erythroblast in vitro culture technology together with a targeted array-based high throughput screening system and discovered more than 30 genes that have novel functions in the early and late stages of terminal erythropoiesis. Among these genes, we identified pleckstrin-2 (plek2), which was previously reported to be involved in T-cell cytoskeleton reorganization, 23 play critical roles in terminal erythropoiesis. We demonstrated that plek2 is important in the regulation of actin cytoskeleton, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 49 publications
(60 reference statements)
4
42
0
Order By: Relevance
“…We previously discovered that Plek2 plays important roles in erythroblast survival and enucleation in the early and late stages of terminal erythropoiesis, respectively (17). In that report, we also found that the Plek2 level is V617F driver mutation of JAK2 is the leading cause of the Philadelphia-chromosome-negative myeloproliferative neoplasms (MPNs).…”
Section: V617fsupporting
confidence: 57%
See 3 more Smart Citations
“…We previously discovered that Plek2 plays important roles in erythroblast survival and enucleation in the early and late stages of terminal erythropoiesis, respectively (17). In that report, we also found that the Plek2 level is V617F driver mutation of JAK2 is the leading cause of the Philadelphia-chromosome-negative myeloproliferative neoplasms (MPNs).…”
Section: V617fsupporting
confidence: 57%
“…This interaction prevents cofilin's localization in mitochondria and thereby protects erythroid progenitors from cell death in the oxidative environment found in the early stage of terminal erythropoiesis (17). We were surprised that Plek2-knockout mice did not show significant anemia at a young age.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These include genes involved in EpoR signaling, enucleation, 61,62 and stress erythropoiesis 63 (Table 2). PLEK2 (Pleckstrin-2) and DYRK3 both have proven roles in terminal erythroid differentiation, 63,64 and both are expressed at ,10% of wildtype levels in the proband. There is KLF1 occupancy of the DYRK3 gene promoter ( Figure 5E).…”
Section: Klf1 Regulates Key Cell-signaling Moleculesmentioning
confidence: 99%